Wykorzystanie tutoringu w procesie wspomagania rozwoju umiejętności życiowych u uczniów z lekką niepełnosprawnością intelektualną = Tutoring as a supporting tool in development of everyday life skills of children with mild mental retardation - Korzeniowska, Regina (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The teacher who works with mentally retarded children should not only conduct the given curriculum. In organising his or her work one should also consider developing their students` skills which will allow them to take active part in everyday social life. It is crucial to provide the pupils with skills and knowledge that would let them be full members of society.
Keywords: umiejętności życiowe; tutoring; uczeń z lekką niepełnosprawnością intelektualną; everyday life skills; student/children with mild mental retardation